PV panel for self-consumption in public buildings - Monteiro, Ana Catarina (2018)
Nowadays, it is imperative to use renewable energy as a source for electricity generation. Energy production by self-consumption and lower costs photovoltaic (PV) panels has created a market for an increase in distributed PV generation. A self-consumption unit may waste almost all-day production if it doesn't match consumption and if there are no batteries in the system. In this case, most part of the energy generated is sold to the public grid. To avoid this situation, these panels should be installed, not in habitation houses, but in people's workplace, that is, public buildings, where photovoltaic production coincides with the load diagram peak of the building, reducing the amount of energy sold to the public grid. In addition, electricity generation decentralization avoids energy losses during transportation and distribution and reduces the number of large electrical plants, significantly contributing to the success of Paris Conference targets that are intended to slow down climate change. In summary, the main objective of this work is to study and evaluate the economic and energy impacts of photovoltaic panels installed in public buildings. Specifically, profitability study of a facility, which is very positive with an IRR of 14, % and an 8-year pay-back.